Research hotspots and trends in robot-assisted surgery in pediatric urology: a bibliometric review based on CiteSpace visual analysis - He, Jingyi; Luo, Diyi (Frontiers in Pediatrics, 2026)
ObjectiveThis study aims to analyze the global research landscape of robot-assisted surgery in pediatric urology, identify developmental trends through visualization methods, and provide references and recommendations for future research directions.MethodsA retrospective bibliometric analysis was conducted using literature retrieved from PubMed and Web of Science Core Collection, covering the period from January 2005 to March 2025. CiteSpace 6.4.R1 software was used for data processing and visualization. Analyses included publication trends, keyword co-occurrence, keyword clustering, and burst detection to construct knowledge maps and explore research dynamics.ResultsA total of 498 publications were included in the analysis. The number of publications showed a clear upward trend. The author collaboration network was relatively dense, with an identifiable core research team. The University of Chicago emerged as the leading institution in terms of publication volume in the field of robot-assisted surgery in pediatric urology. Gundeti MS was the most productive author, contributing 51 published papers to the field. Keyword clustering analysis revealed 10 clusters, and burst detection identified 20 keywords with significant citation bursts.ConclusionsCurrent international research primarily focuses on disease classification and surgical techniques in robot-assisted surgery in pediatric urology. Future studies should continue to explore the clinical potential of robot-assisted surgery, broaden its application scope, and promote the diversified development of pediatric urology.